2015
DOI: 10.1093/mnras/stv210
|View full text |Cite
|
Sign up to set email alerts
|

Spectropolarimetric monitoring of active galaxy 3C 390.3 with 6-m telescope SAO RAS in the period 2009–2014

Abstract: Here we present the spectropolarimetric observations of the radio loud active galaxy 3C 390.3 in the period 2009-2014 (24 epochs). The galaxy has been observed with the 6-meter telescope of SAO RAS using the SCORPIO spectropolarimeter. We explore the variability and lags in the polarized light of the continuum and broad Hα line. We give the Stokes parameters Q, U , degree of linear polarization P and the position angle of the polarization plane, ϕ, for 24 epochs.We find a small lag (10-40 days) between the unp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 60 publications
(118 reference statements)
1
16
0
Order By: Relevance
“…To address such situation, we proposed a hybrid method to detect unknown weak periodic signals in the AGN light curves, which is a modification of the recently proposed timing methods used Hα Dietrich et al 1998Shapovalova et al 2010Sergeev et al 2011Dietrich et al 2012Afanasiev et al 2015 50000 51000 52000 53000 54000 55000 56000 JD -2400000 in geophysics (Pering et al 2014) and acoustics research (Yang & Tse 2005 Kaspi et al 1996Shapovalova et al 2010Bon et al 2012 47000 48000 49000 50000 51000 52000 53000 54000 JD -2400000 for investigation of transient or unstable periodic phenomena), and Spearman correlation technique that accounts for non-linearity and variable amplitude of the wavelet coefficients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address such situation, we proposed a hybrid method to detect unknown weak periodic signals in the AGN light curves, which is a modification of the recently proposed timing methods used Hα Dietrich et al 1998Shapovalova et al 2010Sergeev et al 2011Dietrich et al 2012Afanasiev et al 2015 50000 51000 52000 53000 54000 55000 56000 JD -2400000 in geophysics (Pering et al 2014) and acoustics research (Yang & Tse 2005 Kaspi et al 1996Shapovalova et al 2010Bon et al 2012 47000 48000 49000 50000 51000 52000 53000 54000 JD -2400000 for investigation of transient or unstable periodic phenomena), and Spearman correlation technique that accounts for non-linearity and variable amplitude of the wavelet coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…1), we combined datasets of Shapovalova et al (2013Shapovalova et al ( , spanning the period of 1987Shapovalova et al ( -2010 and Sergeev et al (2000Sergeev et al ( , covering the period of 1992Sergeev et al ( -1996; (iii) For 3C 390.3, Fig. 2, the used observations are from Dietrich et al (1998Dietrich et al ( , covering period 1994Dietrich et al ( -1995, Dietrich et al (2012, covering period from September till December 2005), Shapovalova et al (2010aShapovalova et al ( , covering period 1995Shapovalova et al ( -2007, Sergeev et al (2011Sergeev et al ( , covering period 2000Sergeev et al ( -2007 and Afanasiev et al (2015Afanasiev et al ( , covering period 2009Afanasiev et al ( -2014. Due to complexity of this object, it might be useful to search for periodicity information hidden in the other wavebands, i. e. the continuum 1370 Å, Lyα and CIV lines collected by IUE satellite from 1978-1992(Wamsteker et al 1997) and from 1994December to 1996March (O' Brien et al 1998 (iv) For NGC 4151, Fig.…”
Section: The Light Curvesmentioning
confidence: 99%
“…in several papers, the different polarized line profiles and polarization angles indicate different BLR geometries (see e.g. Afanasiev, Shapovalova, Popović, & Borisov, 2015;Jiang et al, 2021), from outflows to the warped disc-like BLRs.…”
Section: Broad Line Polarization In the Case Of Different Blr Geometr...mentioning
confidence: 98%
“…The velocity resolved RM yields an amazing variety of velocity fields for different objects (e.g., Grier et al, 2013;Peterson, 2017). The evidence favoring a rotational component has been steadily growing, in part due to deep, single-epoch spectropolarimetric observations (e.g., Smith et al, 2005;Afanasiev et al, 2015) that revealed the polarization vector changes expected from the Keplerian velocity field as seen from an equatorial scatter. Systematic outflows have been made evident by the ubiquitous blueshifts of the CIVλ1549 emission line.…”
Section: The Structure Factormentioning
confidence: 99%